Analysis of Ice Supply Needs for Purse Seine Ship Operations in Kutaraja Ocean Fishing Port, Aceh Province - Adha, Ridho; Zain, Jonny; Brown, Arthur (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2023)
This research was conducted in March 2022 at Kutaraja Ocean Fishing Port, Banda Aceh City, Aceh Province. The purpose of the study was to determine what factors determine the amount of ice carried for fishing operations on purse seine fishing gear, and how the relationship between these factors and the amount of ice carried. The method used in this research is the survey method. The data collected were statistically analyzed using the normality test, multicollinearity, ANOVA, Multiple linear regression, and T-Test. The results showed that the size of the ship (X1), the length of the trip (X2), and the amount of catch (X3) affect the amount of ice carried (Y) by purse seine vessels in the form of multiple regression equation Y = 2403.052 - 100.725 X1 + 294.378 X2 + 1.686 X3. The value of the determinant coefficient obtained is 59.4%.